دراسة أنظمة البناء السكنية في مدينة اللاذقية ما بين التنظيم الإداري والمضمون الفني - مزيق احسان (Latakia University Journal -Engineering Sciences Series, 2021)
This research consists of tow parts, The first one discus the structure of urbanism and building process management in Syria, Because building codess in Lattakia city linked hierarchy with integrated system on the level of Syrian state, and it couldnot studied without it alone in administrative and urbanism way, We talk about the Actors in this process and their mutual relations with each other, and analyze these relationships and this structure, and find strengths and revelations to maintain and develop them, Then find faults and negatives of these relationships in order to avoid them And finding effective solutions to it and as a result reaching the goal of raising the efficiency of these relationships and the structure,and reaching to prposals and recommendations to improve it and the relationship between its consists. As for the second part of the research, it briefly reviews residential building codes in Latakia, the most important of which is the building control system and the investment factor system, where it focuses on the technical requirements of these codes, then the research uses the observational method through field monitoring of many residential buildings in one of the regieons in Latakia city, that forme study case, that reflect the statue in the organized regions inside the city that resemblance to large extent in between it, which are subject to two codes mentioned above, to show the fults in applying the technical conditions, from tender and studay stage to execution and investming stage , and this part reach to suggest devlope building codes itself.